"CARE"Less - Aremeyaw Anas, Anas (Ghana, 2015)
The filmmaker goes undercover as a volunteer in an Orphanage home in Bawjiase, to expose the mistreatment of orphans in one of Ghana’s largest privately run orphanages.
Verzio Film Festival Submission
Keywords: Documentary films